Islamic Intellectual Traditions and Their Relevance to Educational Institutions in Indonesia - Sri Maryati (Sustainable, 2023)
This article aims to find out what Islamic intellectual traditions are inherited and the relevance of these traditions to educational institutions in Indonesia today. The article is expected to be useful in adding to the treasures of historical studies and intellectual traditions, as well as these traditions contribute to the preservation of scholarship that existed in the past and see the development of Islamic intellectual traditions today. Islamic intellectual tradition is built on the development of science. Previous scientists inherited the Islamic intellectual tradition, and it is still going on today, especially in the territory of Indonesia. This article attempts to elaborate and show that Islam has an important role to play in establishing the intellectual tradition of Islam today through various lines. It is undeniable that the Islamic intellectual tradition has progressed, sustained by both formal and informal institutions, which began through teaching in huts and pesantren. Islamic intellectual traditions developed with complex variants in the form of traditions covering various Islamic scientific disciplines such as jurisprudence, theology, Sufism, and so on. The process of intellectual tradition takes place in educational institutions today in the form of developing and thinking inherited from intellectuals in the past, such as tradition, memorizing, writing, researching, scientific rihlah, building libraries and formal/non-formal education centers so as to have involvement in the emergence of ideas of the Islamic intellectual tradition today.